CD47 promotes the proliferation and migration of adamantinomatous craniopharyngioma cells by activating the MAPK/ERK pathway, and CD47 blockade facilitates microglia‐mediated phagocytosis. (23rd February 2022) - Zhang, Huarong; Wang, Chaohu; Fan, Jun; Zhu, Qianchao; Feng, Yiwen; Pan, Jun; Peng, Junxiang; Shi, Jin; Qi, Songtao; Liu, Yi
Abstract: Aims: CD47 is overexpressed in multiple tumours and plays an important role in immune escape and other biological processes of tumours. However, its role in adamantinomatous craniopharyngioma (ACP) remains unclear. Therefore, we explored the functions of CD47 in ACP. Methods: In this study, the expression of CD47 and the infiltration of immune cells in ACP was determined by immunohistochemistry (IHC) or immunofluorescence. Microglia‐mediated phagocytosis was analysed using an in vitro phagocytosis assay. Using lentivirus transfection, CD47 was either silenced or overexpressed in primary ACP cells and the biological effects of CD47 on these cells were evaluated in vitro using cell viability, flow cytometry, wound healing, Transwell migration and 3D hydrogel assays. The protein expression levels were analysed by western blotting. Results: Finger‐like protrusions, which may be the key factor in the recurrence of ACP, were primarily found in the region of hypothalamic involvement. The expression of CD47 was higher in palisading epithelium compared with stellate reticulum and epithelial whorls. An in vitro phagocytosis assay showed that CD47 blockade could promote microglia‐mediated phagocytosis. Functional assays revealed that CD47 promoted the growth, migration and invasion of ACP cells in vitro. Our mechanistic investigations showed that CD47 activated the MAPK/ERK pathway, thereby facilitating the biological behaviour of ACP cells. Conclusions: Here, we demonstrated that CD47 plays an important role in ACP cells, suggesting that CD47 could be a new potential therapeutic target for ACP, and adding to the body of literature a role for the inhibition of MAPK/ERK in ACP. Abstract : Finger‐like protrusions may be the key factor in the recurrence of ACP, which is commonly found in the region where ACP involves hypothalamus. CD47 is highly expressed in the palisading epithelium of the outermost layer of the finger‐like protrusions and promotes adverse biological behaviour of ACP, such as proliferation and migration, possibly by activating MAPK/ERK signalling pathway. CD47 blockade facilitates microglia‐mediated phagocytosis.